Permainan Tradisional sebagai Kegiatan Ekstrakurikuler untuk Meningkatkan Kompetensi Sosial Siswa - Marzoan Marzoan; Hamidi Hamidi (Journal An-Nafs: Kajian Penelitian Psikologi, 2017)
This study aims to improve the ability of students in extracurricular programs to improve the social competence of students in primary schools. In this study, the traditional game to be played is a common game performed by the people in the area around the school, the game of fort and selodor. Both types of traditional games are assumed to have a social interest because it is done in groups that require cooperation. The experimental design used in this study was to design the pretest-posttest control group design, ie experimental design divided into experimental and control groups. Data analysis techniques in this study divided into two stages, the first stage uses the Wilcoxon test, the second stage of the Mann-Withney U Test. The subjects of this study were 40 elementary students in North Lombok Regency divided into two groups, namely 20 people in SD Negeri 4 Gondang as an experimental class and 20 students in SD Negeri 1 Rempek as control class. The social competence in this study is measured by using the scale of social competence. The results of this study were (1) There is a significant difference in social competence in the experimental group between before and after being treated; (2) There were significant differences in social competence between the experimental group and the control group after being treated